Tensions and contradictions in sport's quest for legitimacy as a political actor: the politics of Swedish public sport policy hearings. Issue 4 (2nd October 2017) - Stenling, Cecilia; Sam, Mike
ABSTRACT: The purpose of this paper is to draw attention to and analyse strategic representations and legitimacy production in sport policy advocacy processes. Considering it as a case of public consultation in part made possible by contemporary governing systems, the empirical base of the study is the public hearings with representatives of six parliamentary parties that were arranged by the Swedish Sports Confederation (SSC) prior to the 2014 election to the Swedish parliament. Using verbatim transcripts of these hearings as data and the notion of policy advocacy as institutionally situated production of legitimising accounts, two research questions are addressed: (1) What legitimising accounts are produced and deployed by the SSC during the hearings? (2) To what wider systems of meaning are those legitimising accounts connected and how? The analysis shows three sets of legitimising accounts and how both long-standing and contemporary ideas of the sport–government relationship in Sweden were used as cultural resources in these framing processes. Two aspects of policy advocacy processes arising from the study are discussed. First, the possible reasons for and consequences of the contradictory nature of legitimising accounts advanced, and second the transformations of the institutional conditions of sport that are implied by the emergence of phenomena, such as the hearings under analysis.